Glenohumeral Abduction Contracture in Children with Unresolved Neonatal Brachial Plexus Palsy. (21st January 2015) - Eismann, Emily A.; Little, Kevin J.; Laor, Tal; Cornwall, Roger
Abstract : Background: Following neonatal brachial plexus palsy, the Putti sign—obligatory tilt of the scapula with brachiothoracic adduction—suggests the presence of glenohumeral abduction contracture. In the present study, we utilized magnetic resonance imaging (MRI) to quantify this glenohumeral abduction contracture and evaluate its relationship to shoulder joint deformity, muscle atrophy, and function. Methods: We retrospectively reviewed MRIs of the thorax and shoulders obtained before and after shoulder rebalancing surgery (internal rotation contracture release and external rotation tendon transfer) for twenty-eight children with unresolved neonatal brachial plexus palsy. Two raters measured the coronal positions of the scapula, thoracic spine, and humeral shaft bilaterally on coronal images, correcting trigonometrically for scapular protraction on axial images. Supraspinatus, deltoid, and latissimus dorsi muscle atrophy was assessed, blinded to other measures. Correlations between glenohumeral abduction contracture and glenoid version, humeral head subluxation, passive external rotation, and Mallet shoulder function before and after surgery were performed. Results: MRI measurements were highly reliable between raters. Glenohumeral abduction contractures were present in twenty-five of twenty-eight patients, averaging 33° (range, 10° to 65°). Among those patients, abductor atrophy was present in twenty-three of twenty-five, with adductor atrophy in twelve of twenty-five. Preoperatively, greater abduction contracture severity correlated with greater Mallet global abduction and hand-to-neck function. Abduction contracture severity did not correlate preoperatively with axial measurements of glenohumeral dysplasia, but greater glenoid retroversion was associated with worse abduction contractures postoperatively. Surgery improved passive external rotation, active abduction, and hand-to-neck function, but did not change the abduction contracture. Conclusions: A majority of patients with persistent shoulder weakness following neonatal brachial plexus palsy have glenohumeral abduction deformities, with contractures as severe as 65°. The abduction contracture occurs with abductor atrophy, with or without associated adductor atrophy. This contracture may improve global shoulder abduction by positioning the glenohumeral joint in abduction. Glenohumeral and scapulothoracic kinematics and muscle pathology must be further elucidated to advance an understanding of the etiology and the prevention and treatment of the complex shoulder deformity following neonatal brachial plexus palsy. Level of Evidence: TherapeuticLevel IV . See Instructions for Authors for a complete description of levels of evidence.